The Irish American: a history - Dolan, Jay P. (Bloomsbury Press, 2008)
Follows the Irish from their first arrival in the American colonies through the bleak days of the potato famine, the decades of ethnic prejudice and nativist discrimination, the rise of Irish political power, and on to the historic moment when John F. Kennedy was elected to this highest office in the land